2022
DOI: 10.3390/nu14122410
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Mitophagy Regulated by mTOR Signaling Pathway in Liver Fibrosis Associated with Selenium

Abstract: Background: As a central organ of energy metabolism, the liver is closely related to selenium for its normal function and disease development. However, the underlying roles of mitochondrial energy metabolism and mitophagy in liver fibrosis associated with selenium remain unclear. Methods: 28 rats were randomly divided into normal, low-selenium, nano-selenium supplement-1, and supplement-2 groups for a 12-week intervention. We observed pathological and ultrastructural changes in the liver and analyzed the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Importantly, deficient mitophagy in hepatocytes has been associated with the development of liver disease, so targeting mitophagy presents itself as a promising therapeutic target. A protective effect of mitophagy—regulated by the mTOR signaling pathway—has been described in a rat model of liver fibrosis associated with selenium deficiency [ 108 ]. Similarly, melatonin was seen to enhance mitophagy and mitochondrial biogenesis while diminishing liver fibrosis in rats [ 109 ].…”
Section: Novel Therapeutic Approaches Targeting Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, deficient mitophagy in hepatocytes has been associated with the development of liver disease, so targeting mitophagy presents itself as a promising therapeutic target. A protective effect of mitophagy—regulated by the mTOR signaling pathway—has been described in a rat model of liver fibrosis associated with selenium deficiency [ 108 ]. Similarly, melatonin was seen to enhance mitophagy and mitochondrial biogenesis while diminishing liver fibrosis in rats [ 109 ].…”
Section: Novel Therapeutic Approaches Targeting Oxidative Stressmentioning
confidence: 99%
“…In this regard, it has recently been demonstrated that mito-DAMP released from injured mitochondria in hepatocytes directly activate HSC in a liver fibrosis resistant/susceptible mouse strain system. In addition, circulating mito-DAMP were markedly increased in two cohorts of patients with NASH and liver fibrosis; the majority of them had active NASH, defined histopathologically as NAFLD activity score (NAS) ≥ 4, and various degrees of fibrosis ranging from F0 (no fibrosis) to F4 (cirrhosis) [ 108 ]. Of note, circulating mtDNA levels were increased in patients with active NASH (NAS score 4–8, versus NAS score 0–3) and particularly in those with significant histological signs of fibrosis (F2–4) on biopsy, compared to patients with minimal/no fibrosis [ 112 ].…”
Section: Novel Therapeutic Approaches Targeting Oxidative Stressmentioning
confidence: 99%
“…Untargeted metabolomic analysis after Se supplementation have been performed using mice models [47,73,[85][86][87][88][89][90][91][92][93][94][95][96][97][98], pigs [99][100][101][102], broilers [103], cells [104], rats [105][106][107], gazelle [108], zebra fish [109], humans [110], donkeys [111], salmon [112], and catfish [113]. These studies reported a wide range of altered metabolites after Se supplementation focused on liver [73, 91, 94-96, 100-102, 105, 112] and plasma/serum metabolism [73,92,96,101,105,108,110], but also in muscle [99,103], kidneys [73,93], testes [73], lungs [73,90], spleen [96], blood…”
Section: Metabolomic Studies Related To the Impact Of Dietary Seleniu...mentioning
confidence: 99%
“…A summary of the metabolomics studies reported after Se supplementation using different analytical platforms is shown in Table 2. As can be seen, metabolomics is usually combined with transcriptomics [47,90,94,99,101,103,109,111], histopathology [98,103,106,109], metallomics [73,90,91,98,99,105,107], proteomics [96,101], enzymatic activities [91,97,98], or targeted metabolomics [100,109]. Several studies focused on metataxonomics and gut metabolomics [95,96,101,106,113].…”
Section: Metabolomic Studies Related To the Impact Of Dietary Seleniu...mentioning
confidence: 99%
See 1 more Smart Citation